2006
DOI: 10.1002/app.25174
|View full text |Cite
|
Sign up to set email alerts
|

A very simple empirical kinetic model of the acid‐catalyzed cure of urea–formaldehyde resins

Abstract: ABSTRACT:The hot pressing operation is the final stage in MDF (medium density fiberboard) manufacture; the fiber mat is compressed and heated up to promote the cure of the resin. The aim of the investigations is to study the curing reactions of UF (Urea-Formaldehyde) resins as commonly used in the production of MDF, and to develop a simplified kinetic model. This investigation has combined Raman spectroscopy to study the reaction cure and 13 C-NMR for the quantitative and qualitative characterization of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Various analytical methods have been applied to investigate the structure of compounds formed during the UF resin synthesis including elemental analysis,4,5 thin‐layer chromatography,6–8 liquid chromatography,9,10 infrared spectroscopy techniques,11,12 Raman spectroscopy, mass spectrometry, and NMR spectroscopy 13–22. A detailed overview on the efforts and methods used to characterize UF resins is given by Carvahlo et al23 Using NMR spectroscopy Tomita and Hatono15 confirmed the existence of internal methylene ether bridges, cyclic uron derivatives, in UF resins and referenced their chemical shifts. More recently, 13 C‐NMR studies24,25 proved that strong acidic conditions (and pH higher than 6, ref 24…”
Section: Introductionmentioning
confidence: 99%
“…Various analytical methods have been applied to investigate the structure of compounds formed during the UF resin synthesis including elemental analysis,4,5 thin‐layer chromatography,6–8 liquid chromatography,9,10 infrared spectroscopy techniques,11,12 Raman spectroscopy, mass spectrometry, and NMR spectroscopy 13–22. A detailed overview on the efforts and methods used to characterize UF resins is given by Carvahlo et al23 Using NMR spectroscopy Tomita and Hatono15 confirmed the existence of internal methylene ether bridges, cyclic uron derivatives, in UF resins and referenced their chemical shifts. More recently, 13 C‐NMR studies24,25 proved that strong acidic conditions (and pH higher than 6, ref 24…”
Section: Introductionmentioning
confidence: 99%
“…The results are shown in Table 1 . The assignment of the chemical shifts were made based in articles of UF resins [ 18 , 19 ] and articles with 13 C NMR analysis of DMeU with formaldehyde [ 8 , 20 ]. The peaks present a little shift to the right due to the high DMSO- d 6 content [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The complex structure and chemistry of UF resins has been subject of numerous research studies, but their physical, morphological, and chemical properties are not yet fully understood. The large variety of structural elements such as methylene bridges, ether bridges, methylol and amide groups or possible cyclic compounds makes their analysis very difficult . In the same way, the effect of changing synthesis parameters (for example, pH, temperature, F / U molar ratios) on the chemical structure of the resin has not been well established.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this analytical method allows the identification of several functional groups present in the resins and its quantitative determination . Over the years, many works have been performed by different researchers using 13 C NMR to identify the chemical structure of UF resins synthesized under different pH conditions . Some authors have shown that uronic structures are present in the resins when strongly acidic conditions are employed.…”
Section: Introductionmentioning
confidence: 99%